Differential Lectin Agglutination of Fetal, Dividing-Postnatal, and Malignant Hepatocytes - Becker, F. F. (1974)
Numerous studies have reported the capacity of the lectin, concanavalin A, to agglutinate selected cell-types. The finding that cells transformed in culture, embryonic cells, and malignant cells are all agglutinated by this substance, may contribute to our understanding of the oncogenic process. The present study compared the response to concanavalin A of rat hepatocytes derived from livers of differing developmental and mitotic-status as well as those derived from malignant liver tumors (hepatomas). Fetal hepatocytes and hepatoma cells were highly susceptible to agglutination while hepatocytes from post-natal livers, whether dividing or quiescent, were not. Treatment with protease(s) did not make the interphase hepatocyte agglutinable. These data emphasize the importance of examining a wide variety of cells in attempting to understand the interaction of lectins on cell surfaces, and further, demonstrate the value of obtaining cells directly from tissue(s) during differing physiologic and pathologic states.